DARI NILAI KE TINDAKAN: TANTANGAN PENILAIAN KARAKTER DALAM PEMBELAJARAN PPKN DI SD NEGERI 1 MUNENG - Laela Rosidha; Sulton (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to analyze character assessment practices in Pancasila and Citizenship Education (Pendidikan Pancasila dan Kewarganegaraan/PPKn) at SD Negeri 1 Muneng. This research is motivated by a prevalent issue in elementary education: the dominance of cognitive assessment and the limited implementation of affective or character assessment. Conversely, in alignment with the Merdeka Belajar (Freedom to Learn) paradigm, Citizenship Education should emphasize strengthening Pancasila values through contextual learning experiences oriented toward behavioral formation. This study employs a descriptive qualitative approach with a single case study design. Data were collected through observation, in-depth interviews with teachers and the principal, and document analysis of instructional materials. Data were analyzed thematically following the Miles and Huberman model, encompassing data reduction, data display, and interactive conclusion drawing. The results indicate that character assessment at SD Negeri 1 Muneng remains heavily focused on the cognitive dimension through written tests and daily quizzes. Attitude assessment is conducted via observation without standardized rubrics, rendering the results subjective and unsystematically documented. However, the school demonstrates a strong commitment to character building through value-based intracurricular, co-curricular, and extracurricular activities, such as morning literacy, majase (healthy snack consumption), and the Profil Pelajar Pancasila project. Supporting factors include a religious and collaborative school culture, while the primary obstacle is the limited teacher competence in implementing authentic assessment. These findings corroborate previous studies by Komalasari & Saripudin (2020) and Rusmin et al. (2020), indicating that character assessment is effective when teachers possess a reflective understanding of the values internalized during the learning process. The implications of this study underscore the necessity of teacher training in developing Pancasila-based character assessment instruments and enhancing academic supervision to ensure alignment between the school's vision and assessment practices. Theoretically, this study enriches the literature on character assessment in elementary education, while practically offering concrete recommendations for developing more objective, contextual, and sustainable character assessment systems.